1981
DOI: 10.1002/jcu.1870090504
|View full text |Cite
|
Sign up to set email alerts
|

Medical implications of ultrasonically detected polycystic ovaries

Abstract: Polycystic ovaries are usually manifest on an ultrasound study as symmetrically enlarged ovaries containing numerous tiny cysts. The cysts are difficult to detect with conventional contact B-scanners but are readily detected with high-resolution, real-time sector scanners. The cysts range in diameter form 2 to 6 mm and may be arranged in the periphery of an ovary or throughout the parenchyma. In patients with ultrasonically demonstrated polycystic ovaries (aged 15 to 35 years), there is a spectrum of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1
3

Year Published

1982
1982
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(92 citation statements)
references
References 9 publications
2
86
1
3
Order By: Relevance
“…We measured the length of the uterus and calculated the ovarian volume using the simplified formula for a prolate ellipsoid [22]. …”
Section: Methodsmentioning
confidence: 99%
“…We measured the length of the uterus and calculated the ovarian volume using the simplified formula for a prolate ellipsoid [22]. …”
Section: Methodsmentioning
confidence: 99%
“…When the presence of PCOS is defined solely by the finding of polycystic ovaries at either surgery or sonography, between 1-20% of unselected women have been reported to be affected (10 -13). However, this marker is relatively nonspecific, because up to 25% of patients with this ovarian morphology on sonography are asymptomatic (14). In addition, not all patients with hyperandrogenic oligoovulation demonstrate polycysticappearing ovaries (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…The most prominent feature in the ovaries of patients with PCOS was the increase in ovarian volume. Studies based on transabdominal ultrasound have shown that normal ovaries were ellipsoid structures, with aver age volumes between 4.0 and 6.5 ml and the upper limit of ovarian volume between 5.7 and 7.6 ml [11,17,18], The ovarian volumes in patients with PCOS were twice those in normal ovaries, with average ovarian volume rangingfrom 12.0to 16.6 ml [8,10,11,14,[19][20][21], Pache et al [22], using transvaginal ultrasound, reported that the average ovarian volumes in normal women and patients with PCOS were 5.9 and 9.8 ml, respectively. In the present study, the ovarian volume (10.3 ml) observed in patients with PCOS was similarly about twice that (4.5 ml) in normal women and was in accordance with the results of Pache et al [22], Several investigators [10,11,23] have reported that 29-34% of ovaries in patients with PCOS were normal in size.…”
Section: Discussionmentioning
confidence: 99%